2014
DOI: 10.1371/journal.pone.0113274
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice of Public Involvement Activities in Biomedical Research and Innovation: A Systematic Qualitative Review

Abstract: BackgroundA recent report from the British Nuffield Council on Bioethics associated ‘emerging biotechnologies’ with a threefold challenge: 1) uncertainty about outcomes, 2) diverse public views on the values and implications attached to biotechnologies and 3) the possibility of creating radical changes regarding societal relations and practices. To address these challenges, leading international institutions stress the need for public involvement activities (PIAs). The objective of this study was to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Reviewers were not blinded to author, institution, or journal. The agreement was 100% before discussion and 6051 records were excluded leaving n = 39 potentially eligible articles for full‐text screening.…”
Section: Resultsmentioning
confidence: 99%
“…Reviewers were not blinded to author, institution, or journal. The agreement was 100% before discussion and 6051 records were excluded leaving n = 39 potentially eligible articles for full‐text screening.…”
Section: Resultsmentioning
confidence: 99%
“…A previously published analysis on the same sample of PIA reports revealed that translation of PIA results into policy and practice is currently little documented [24]. A more precise reporting of representation objectives, achieved levels of representation and its limitations could contribute to more successful translation of PIA results, since representation ensures that the views, interests and preferences of the population at large are reflected [15].…”
Section: Discussionmentioning
confidence: 99%
“…material, see www.karger.com/doi/10.1159/000444478). For details on the search strategy see [24]. For the subsequent thematic text analysis of selected reports, an assessment matrix was developed based on a literature review of PIA-specific guidelines and frameworks [25,26,27,28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient involvement and participation have been advocated for public health reasons, and found to improve quality of life and health outcomes . Many patients today participate on a system level, as activists involved in political processes, as board members in decisions about organization of health care or in prioritization of new treatments or technologies, in formal education of health professionals, and as researchers in biomedical research …”
Section: Introductionmentioning
confidence: 99%